KATA MAJEMUK DALAM MAJALAH TIME (ANALISIS MORFOLOGIS) - Dondo, Alri Reiza; Lotulung, Donald R; Qarimah, Aryana N (English Study Program, Faculty of Humanities, Universitas Andalas, Padang, 2025)
This study, entitled “Compound Words in Time Magazine (A Morphological Analysis),” aims to identify and classify the types of compound words found in Time magazine. A qualitative descriptive method is employed, and the data are analyzed using the theory of Carstairs-McCarthy (2002:59), which provides a framework for morphological analysis. The data consist of compound words taken from 26 articles in Time magazine. From the analysis, a total of 262 compound words are identified. These include 182 compound nouns, 3 compound verbs, 75 compound adjectives, 1 compound adverb, and 1 compound pronoun. The results indicate that compound nouns appear most frequently in journalistic writing, followed by compound adjectives. This study contributes to a better understanding of how compound words are used in journalistic texts and may serve as a reference for further morphological research or linguistic studies in media language.